Advancements in Real-Time PCR Technologies: A Comprehensive Review of Probe-Based and Non-Probe-Based Assays for Molecular Diagnostics - Malau, Jekmal; Zahro, Aurora Fatimatuz; Zahra, Aliya Azkia; Kasasiah, Ahsanal; Meilani, Nanda Diva; Damara, Dandy Satria; Lestari, Agatha Nabilla; Saryono; Wahyono, Daniel Joko (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2025)
The decision between probe-based and non-probe-based qPCR assays is crucial, influenced by diagnostic goals and sample characteristics. This review provides an in-depth evaluation of these two assay types, analyzing their principles, strengths, drawbacks, and applications. A thorough review of the literature, primarily sourced from PubMed, was undertaken to explore prominent assay systems, including TaqMan, KASP, rhAmp, HRM, and SYBR Green. Probe-based qPCR assays, exemplified by TaqMan and rhAmp, are distinguished by their high specificity, aptitude for multiplex analysis, and reduced risk of false positives, making them highly suitable for SNP genotyping and pathogen detection. However, their elevated costs and intricate design requirements remain significant challenges. Conversely, non-probe-based assays, such as SYBR Green and HRM, present cost-effective alternatives with straightforward designs. HRM, in particular, is effective in identifying genetic variations like SNPs with remarkable sensitivity. Nonetheless, these methods are susceptible to non-specific amplifications, requiring careful optimization to maintain reliability. The selection of a suitable qPCR assay depends on various factors, including precision, affordability, and multiplexing capabilities, with applications spanning infectious disease detection and genetic disorder analysis. This review emphasizes the indispensable role of qPCR in molecular diagnostics while showcasing recent technological advances that aim to mitigate existing constraints and enhance diagnostic precision and accessibility.